Philosophy of Latin America
VIII, 316 p.
Keywords: In most contributions collected in this volume, the influence from European and American philosophy can be felt. Remarkably, ten out of thirteen philosophers feel that the working out of a genuine Latin American local, national and continental cultural identity is a challenge to philosophy. This volume contains articles on topics within a variety of disciplines: political philosophy, ethics, history of philosophy, formal logic, philosophy of science and technology, as well as philosophical interpretation of literature. It is relevant to a large audience of philosophers and researchers in these disciplines.